Antidiabetic and antioxidative effects of Lepisanthes fruticosa fruit seed extract in type 2 diabetic experimental rats - A.H.S., Mirfat; I., Amin; M.A., Mohd Shukri; H., Muhajir; K., Nur Kartinee; M., Syahida; M., Razali (Rynnye Lyan Resources, 2023)
Lepisanthes fruticosa (Roxb) Leenh or locally known as ceri Terengganu is an underutilised fruit species from the Sapindaceae family. The species was previously identified as a potent antioxidant source, but scientific information is still lacking and limited to in vitro. Therefore, the present study aimed to investigate the in vivo antidiabetic and antioxidative effects of L. fruticosa fruit seed extract (LFSE) in a high-fat diet, streptozotocin (HFD/STZ)-induced Sprague Dawley rats. After 8 weeks of HFD feeding, a low-dose STZ (35 mg/kg body weight) was injected to induce type 2 diabetes mellitus (T2DM). Two dosages of LFSE (300 and 600 mg/kg body weight) were orally administered to diabetic rats for 4 weeks. High dosage LFSE (600 mg/kg body weight) showed a more pronounced effect in anti-hyperglycemic activities as indicated by both sub-chronic and acute studies. The glucose-lowering ability of LFSE was supported by its improved serum insulin level (40%) as compared to diabetic control. LFSE (600 mg/kg) also resulted in a significant (P<0.05) increase in superoxide dismutase (SOD) (20%) and catalase (CAT) (43%) activities, with a significant (P<0.05) decrease in lipid peroxidation (28%) as compared to diabetic control. With regard to lipid profile, low dosage LFSE (300 mg/kg) led to a significant (P<0.05) improvement in high-density lipoprotein cholesterol (HDL-c) (39%). Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis of LFSE showed the presence of various phytochemicals with antidiabetic and antioxidant properties, with α-kojibiose, genistein-7,4'-di-O-β-D-glucoside and soyacerebroside II being the predominant ones. The findings may suggest that L. fruticosa fruit seed extract is potential in reducing hyperglycaemia and enhancing antioxidant status in HFD/STZ-induced diabetic rats. Therefore, it can be concluded that L. fruticosa fruit species may be considered as a promising candidate for a new and safe alternative remedy for the prevention and treatment of T2DM.